The Examiner – Back to the Future - Lloyd A. Palans (Washington University Journal of Law & Policy, 2017)
This Article examines the role Judge Barry Schermer played in crafting the role of an examiner under the then-new Bankruptcy Code section 1104(c). Palans revisits Jude Schermer’s appointment of an examiner and the parameters given to that role in In re Apex Oil. The Author concludes Judge Schermer’s authorization to give an examiner a flexible role, empowered in the interest of assisting the parties involved, was a forward-thinking way of setting up an investigator and mediator for the efficient administration of justice.
Keywords: Bankruptcy; Bankruptcy Code; Chapter 11 Bankruptcy; Bankruptcy Examiner; Masters; Federal Rules of Civil Procedure; Federal Rules of Bankruptcy Procedure